HIV MDR is still a relevant issue despite its dramatic drop over the years. (24th January 2020) - Armenia, D; Di Carlo, D; Flandre, P; Bouba, Y; Borghi, V; Forbici, F; Bertoli, A; Gori, C; Fabeni, L; Gennari, W; Pinnetti, C; Mondi, A; et al.
Abstract: Objectives: To evaluate the prevalence and therapeutic relevance of drug resistance among isolates from ART-experienced HIV-1-infected patients over the past two decades in Italy. Methods: Dynamics of resistance to one, two and three or more antiretroviral classes were evaluated from 1999–2018. Virological success (VS) after the latest therapy switch was evaluated according to cumulative class resistance and cumulative genotypic susceptibility score (Stanford HIV_DB algorithm). Results: Among 13 663 isolates (from 6739 patients), resistance to at least one drug class decreased sharply from 1999 to 2010 (≤2001, 84.6%; 2010, 43.6%; P  <   0.001), then remained relatively constant at ∼40% during 2010–18, with the proportion of resistance to three or more classes also stable (∼5%). After 2008, integrase inhibitor resistance slightly increased from 5.6% to 9.7% in 2018 and contributed to resistance, particularly in isolates with resistance to three or more classes (one class, 8.4%; two classes, 15.3%; three or more classes, 34.7%, P  <   0.001). Among 1827 failing patients with an available follow-up, by 1 year after genotype-guided therapy start the probability of VS was 87.6%. Patients with cumulative resistance to three or more classes and receiving a poorly active regimen showed the lowest probability (62.6%) of VS ( P  <   0.001) compared with all other patients (≥81.8%). By Cox regression analysis, cumulative MDR and receiving poorly active antiretroviral regimens were associated with a lower hazard of VS compared with those without resistance. Conclusions: A dramatic drop of HIV-1 drug resistance at failure has been achieved over the last two decades in Italy; resistance to three or more classes is low but present among currently failing patients. Its management still requires a rational and careful diagnostic and therapeutic approach.